TINJAUAN YURIDIS KETENTUAN PASAL 13 AYAT (2) PERATURAN PEMERINTAH REPUBLIK INDONESIA NOMOR 42 TAHUN 2013 TENTANG SYARAT DAN TATA CARA PEMBERIAN BANTUAN HUKUM DAN PENYALURAN DANA BANTUAN HUKUM - Apri Rotin; Sudarman Sudarman (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2018)
Legal assistance is legal services provided by legal aid providers free of charge to legal aid recipients. The recipient of legal aid is the person or group of the poor. While the legal aid providers are legal aid agencies or community organizations that provide legal aid services based on Law Number 16 Year 2011. This legal research focuses more on lecturers and law faculty students as legal aid providers. With the existence of Law No. 16 of 2011 on Legal Aid can open opportunities for students to train lawyers in the Court. This research used normative legal research method, the type of research used is normative juridical, the approach taken is the statutory approach (statute approach) Legal Aid Act exactly explains and expands the parties that can provide legal aid Not only advocates which can provide legal assistance but also paralegals, faculty and law faculty students, the provision of legal aid by lecturers and students of law faculties is an action that must be realized because it is the implementation of the third function of Tri Dharma Perguruan Tinggi, that is the dedication to the society In handling the legal matter communities, paralegals, faculty, and law faculty students are subject to the same procedural law. Keywords:legal aid providers